2011
DOI: 10.1088/0029-5515/51/10/103029
|View full text |Cite
|
Sign up to set email alerts
|

Fast-ion effects during test blanket module simulation experiments in DIII-D

Abstract: Fast beam-ion losses were studied in DIII-D in the presence of a scaled mockup of two Test Blanket Modules (TBM) for ITER. Heating of the protective tiles on the front of the TBM surface was found when neutral beams were injected and the TBM fields were engaged. The fast-ion core confinement was not significantly affected. Different orbit-following codes predict the formation of a hot spot on the TBM surface arising from beam-ions deposited near the edge of the plasma. The codes are in good agreement with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
4
26
0
Order By: Relevance
“…In order to calculate accurately the location where the particle impacts the wall, it is important to take into account the full-particle orbit because the Larmor radius, in this case up to about 4 cm at the point of impact, is comparable or larger than the characteristic TBM field gradient scale lengths near the tile surfaces. The heat loads from the SPIRAL simulations reproduce the measured temperature increase at the back of the 2.5 cm thick protective carbon tiles in the TBM experiments as was reported in [29].…”
Section: Tbm-induced Heat Load Simulationssupporting
confidence: 71%
See 3 more Smart Citations
“…In order to calculate accurately the location where the particle impacts the wall, it is important to take into account the full-particle orbit because the Larmor radius, in this case up to about 4 cm at the point of impact, is comparable or larger than the characteristic TBM field gradient scale lengths near the tile surfaces. The heat loads from the SPIRAL simulations reproduce the measured temperature increase at the back of the 2.5 cm thick protective carbon tiles in the TBM experiments as was reported in [29].…”
Section: Tbm-induced Heat Load Simulationssupporting
confidence: 71%
“…Two examples of toroidal ripple fields are shown in figure 10 where a conventional ripple induced by a finite number of toroidal field coils is shown for NSTX while a localized ripple in DIII-D that was deliberately induced by a set of coils to create the expected (scaled) fields in ITER induced by one pair of TBMs. The fields in DIII-D were used to study the impact of such localized perturbed fields on the plasma performance [28] and first wall heat loads [29].…”
Section: Static Perturbed Magnetic Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…To mimic the ITER fields, the DIII-D installation contains two racetrack coils and a vertical solenoid that are both energized in the present experiment. The amplitude of the perturbed field exceeds the amplitude of a single ITER TBM by a factor of ∌3. Previous experiments found that the mock-up TBM fields degrade both fusion product [4] and beam-ion [5] confinement. During beam injection, localized heating on the graphite tiles that surround the TBM port is observed [5].…”
Section: Introductionmentioning
confidence: 97%